Multiple Intracranial Meningiomas: A Review of the Literature and a Case Report - F. Koech; J. Orege; F. Ndiangui; B. Macharia; N. Mbaruku (Case Reports in Surgery)
Multiple intracranial meningiomas are a condition where there is more than one meningioma in several intracranial locations in the same patient without signs of neurofibromatosis. Incidence varies from 1 to 10%. The prognosis of multiple intracranial meningioma does not differ from benign solitary meningiomas despite the multiplicity. However, the simultaneous occurrence of different grades of malignancy is observed in one-third of multiple meningiomas. Surgery remains the best option for treatment of symptomatic lesions. Our case review aims to present and discuss a 75-year-old female patient diagnosed with multiple intracranial meningiomas, describing their clinical, radiological, histological characteristics. It also highlights the fact that the patient had two tumours, underwent surgery, and so far has a good quality of life.